Carotid magnetic resonance imaging in persons living with HIV and 10-year atherosclerotic cardiovascular disease risk score. Issue 8 (November 2018) - Mee, Thomas C; Aepfelbacher, Julia; Krakora, Rebecca; Chairez, Cheryl; Kvaratskhelia, Nina; Smith, Bryan; Sandfort, Veit; Hadigan, Colleen; Morse, Caryn; Hammoud, Dima A
Background: Both traditional and HIV-specific risk factors contribute to greater incidence of cardiovascular disease in persons living with HIV (PLWH). Using state-of-the-art, high-resolution magnetic resonance (MR) imaging of the common carotid arteries, this study aimed to evaluate the relationship between carotid vessel wall thickness (c-VWT) and atherosclerotic cardiovascular disease (ASCVD) risk score in PLWH. Methods: Cross-sectional determinations of c-VWT using MR imaging in virally suppressed PLWH without known cardiovascular disease ( n =32) and matched controls ( n =13) were completed. Clinical data, including ASCVD risk and c-VWT, were compared between groups and regression analyses performed to identify predictors of c-VWT. Results: PLWH had significantly higher c-VWT (1.15 ±0.11 mm versus 1.08 ±0.08 mm; P =0.02) as well as higher diastolic blood pressure compared to controls, but exhibited no differences in 10-year ASCVD risk score, systolic blood pressure or smoking. Ten-year ASCVD risk score (r=0.53, P -value =0.0002), age (r=0.30, P -value <0.05), triglycerides (r=0.33, P -value =0.03) and waist circumference (r=0.36, P -value =0.02) were significantly associated with increased c-VWT. Among PLWH, c-VWT did not differ by protease inhibitor use. In a multivariate regression analysis, ASCVD risk score was the only variable significantly associated with c-VWT ( P -value =0.02), whereas, HIV status was not. Conclusions: In this cross-sectional study MR imaging demonstrated that c-VWT, a known marker for CVD risk, was increased in PLWH relative to controls, and that 10-year ASCVD risk was closely related to c-VWT, independent of HIV infection. Our data suggest that traditional cardiovascular disease risk factors in PLWH are adequately captured in the ASCVD risk score which was closely associated with subclinical carotid disease.